Standardized Asthma Admission Criteria Reduce Length of Stay in a Pediatric Emergency Department. (13th February 2016) - Rutman, Lori; Migita, Russell; Spencer, Suzanne; Kaplan, Ron; Klein, Eileen J.
Abstract: Objectives: Asthma is the most common chronic illness in children and accounts for > 600, 000 emergency department (ED) visits each year. Reducing ED length of stay (LOS) for moderate to severe asthmatics improves ED throughput and patient care for this high‐risk population. The objective of this study was to determine the impact of adding standardized, respiratory score–based admission criteria to an asthma pathway on ED LOS for admitted patients, time to bed request, overall percentage of admitted asthmatics, inpatient LOS, and percentage of pediatric intensive care unit (PICU) admissions. Methods: This was a retrospective study of a quality improvement intervention. Statistical process control methodologies were used to analyze measures 15 months before and after implementation of a modified asthma pathway (June 2010 to December 2012; pathway modification September 2011). Results: A total of 3, 688 patients aged 1 through 18 years who presented to the ED with an asthma exacerbation during the study period were included. Patients were excluded if they were not eligible for the asthma pathway. Patient characteristics were similar before and after the intervention. Mean ED LOS and time to bed request for admitted asthmatics both decreased by 30 minutes. There was no change in percentage of asthma admissions (34%), mean inpatient LOS (1.4 days), or percentage of PICU admissions (2%). Conclusions: Standardizing care for asthma patients to include objective admission criteria early in the ED course may optimize patient care and improve ED flow.